Osteoresorptive arsenic intoxication - Dani, Sergio U. (Bone, 2013)
A 47-year-old woman consulted her dermatologist complaining whole body dermatitis, urticaria and irritating bullous eruptions on the plantar and side surfaces of her feet. She had had multiple hypopigmented spots on her skin since her early adulthood. The patient was treated with topical medication without significant improvement of symptoms. One year later she suffered a myocardial infarction, accompanied by refractory anaemia. At the age of 49, a breast cancer was diagnosed and shortly thereafter her last menstruation occurred. At age 50years, upon complaint of weight loss despite normal food intake, Hashimoto thyroiditis with latent hyperthyroidism, vitamin D insufficiency with secondary hyperparathyroidism, and poikilocytic anaemia with anisochromia, hypochromia, anisocytosis, elliptocytes, drepanocytes, dacryocytes, acanthocytes, echinocytes, schizocytes, stomatocytes and target cells were diagnosed. The osteodensitometric and laboratory examinations revealed osteoporosis with sustained elevation of urinary Dipyridinolin-crosslinks (u-Dpd), and urinary arsenic (u-As) of 500μg/l (equivalent to 0.5 parts per million-ppm, 2.5μg/mg creatinine/dl, u-As: Phosphate of 26μg/mmol; the estimated bone As:P and As/kg body weight were 500μg/g and 11.3mg/kg, respectively). Thalassemia, immunoglobinopathy and iron deficiency were excluded. Supplementation with oral vitamin D and calcium, and antiresorptive therapy with intravenous zolendronate normalised the u-Dpd, significantly decreased the urinary arsenic concentration, and cured the anemia and the urticaria. A diagnosis of osteoresorptive arsenic intoxication (ORAI) was established.
Gesehen am 09.06.2021